Cultural history in the context of history of culture - O. Y. Pavlova, (Ukrainian Cultural Studies, 2021)
The article is devoted to the definition of basic concepts and methodological principles of the organization of the humanities, in particular culture studies in a diachronic perspective. The shift of the field of cultural research in the process of understanding its historical principles is studied. In particular, there is a pattern of shifting humanities knowledge from direct identification with the field of "human sciences" ("Geisteswissenschaften") to the study of the fundamental multiplicity of human way of life, and, accordingly, exposing the transcendental status of culture and the need to understand the basic principles of interaction of different cultures in the diachronic dimension. Recognition of the original guideline of cultural diversity presupposes a rethinking of the historical sequence as an evaluative guideline, but, on the other hand, the avoidance of a futile denial of the principle of historicism in general. Thus, understanding the history of culture requires the study of cultural history as the basis of historical understanding of the very knowledge of culture.In general, the discipline – the history of culture or even "history of cultures" is derived from the concept of culture as a whole in two dimensions: defining the scope and content of the term "culture". As well as the recognition of its original non-homogeneity, and hence the need for reflection on the basic principles of its classification; the initial guideline for cultural diversity provides for the possibility of defining not only a synchronous but also a diachronic perspective;Thus, cultural history is a theoretical field of cultural research, which captures, comprehends and formulates the subject field and methodological guidelines for understanding the historical dynamics of culture in its correlation with the content of basic concepts. Thus, the subject field of cultural history implicitly provides the context of the history of culture, and the history of culture – the need to reflect on the order of organization of their theoretical and empirical guidelines.
Keywords: history of culture, cultural history, context, culture, interaction of cultures, diachrony